The disconnect between individual-level and population-level HIV prevention benefits of antiretroviral treatment. Issue 9 (September 2019) - Baral, Stefan; Rao, Amrita; Sullivan, Patrick; Phaswana-Mafuya, Nancy; Diouf, Daouda; Millett, Greg; Musyoki, Helgar; Geng, Elvin; Mishra, Sharmistha
Summary: In 2019, the HIV pandemic is growing and soon over 40 million people will be living with HIV. Effective population-based approaches to decrease HIV incidence are as relevant as ever given modest reductions observed over the past decade. Treatment as prevention is often heralded as the path to improve HIV outcomes and to reduce HIV incidence. Although treatment of an individual does eliminate onward transmission to serodifferent partners (undetectable=untransmittable or U=U), population-level observational and experimental data have not shown a similar effect with scale-up of treatment on reducing HIV incidence. This disconnect might be the result of little attention given to heterogeneities of HIV acquisition and transmission risks that exist in people at risk for and living with HIV, even in the most broadly generalised epidemics. Available data suggest that HIV treatment is treatment, HIV prevention is prevention, and specificity of HIV treatment approaches towards people at highest risk of onward transmission drives the intersection between the two. All people living with HIV deserve HIV treatment, but both more accurately estimating and optimising the potential HIV prevention effects of universal treatment approaches necessitates understanding who is being supported with treatment rather than a focus on treatment targets such as 90-90-90 or 95-95-95.